Medical Informatics and Problem-based Learning - Hasman, A.; Boshuizen, H. P. A. (Methods of Information in Medicine, 2001)
Problem-based learning (PBL) is an educational method that can be considered as an alternative to the traditional, discipline-based, approach to teaching. In this paper the characteristics of both approaches are discussed and compared. Some background knowledge concerning the principles that determine the success of instructional methods is presented. Finally, it is discussed how medical informatics can be taught in a PBL environment.
Keywords: Problem-based Learning; Instructional Methods; Medical Informatics Education; Discipline-based Teaching